Pattern of Healthcare-Associated Infections in a Tertiary Care Setting - Tariq, Anam; Mirza, Irfan Ali; Fahim, Qanita; Hameed, Fatima; Khalid, Ayesha; Ashfaq, Ambar (Pakistan Armed Forces Medical Journal, 2024)
Objective: To establish the frequency of emerging pathogens and their susceptibility profiles amongst various healthcare-associated infections.Study Design: Cross-sectional study.Place and Duration of Study: Department of Microbiology, Combined Military Hospital, Lahore Pakistan, from Jan to Dec 2020.Methodology: One hundred and ninety-six samples with a history of hospital-acquired infections were received and processed following standard microbiological techniques. Antibiotic susceptibility testing was done by the Kirby-Bauer Disk Diffusion technique for the commonly used antibiotics. For colistin susceptibility, the Clinical and Laboratory Standards Institute recommends broth microdilution, colistin broth disk elution, or colistin agar testing MIC methods, however, colistin susceptibility was performed by the E-strip method.Results: One hundred and ninety-six clinical samples with bacterial isolates causing healthcare-associated infections were processed. Specimens were from patients with surgical site infections (59,30.1%), Catheter-associated bloodstream infection (52, 26.5%); Ventilator-associated pneumonia (48, 24.5%) and Urinary tract infection (37,18.9%). Klebsiella pneumoniae (64, 32.7%), E.coli (51, 26%) and Acinetobacter baumanii (45,23%) were the leading bacterial pathogens. A total of 72(36.7%) isolates showed multidrug resistance whereas extensively drug-resistant isolates were calculated to be 124(63.3%).Conclusion: High level of bacterial resistance amongst common health-care-associated infections is an eye-opener and impacts applying strict infection control measures along with antimicrobial stewardship. It will also help clinicians modify empiric treatment regimes in affected patients.